A voz na mise en scène: o filme Cidade de Deus sob a escuta fonoaudiológica - Amaral, Vitória Rocha Prado (2006)
Introduction: The elements of movie language are creatively combined together and from this relationship, new meanings are created. All these elements form the mise en scène. Objective: Based on the investigation of the movie production City of God, the purpose of the present study was to analyze how voice - loudness, speed, intonation, prolongation and pauses - is related with the other elements of movie language - interpreting, scenic design, lighting design, costumes, colors, camera speed and movement, editing, soundtrack and other sounds effects - in three excerpts of the movie and to check the effects of this relationship with the creation of the mise en scène. Method: The first part was a Survey of the Context of the film City of God referring to the investigation of pre-production, production and post-production, including interviews with the speech and voice therapists that worked for the movie. The second part shows the Analysis of Excerpts of the movie in which the analyzed elements of the visual dimension were: camera (movement, speed, plans), art (scenic design, colors, lighting design), costumes and editing, and the elements of auditory dimension were: voice (loudness, speed, intonation, prolongation and pauses), sound effects and soundtrack. Results: The authors did not work with the script and for this reason they did not memorize or mark actions or vocal resources. It was a free work that valued the performance of each actor, and the other elements got adapted to the interpretation. Speech and voice therapists worked with the voice of some authors so that they could make themselves understood in spite of articulation and voice projection problems. In Excerpt 1, there is an intrinsic relationship of speed, loudness and intonation and camera movement, pace of interpreting, editing, colors, lighting design, costumes, soundtrack and sound effects. In Excerpt 2, voices follow the pace of interpretation and editing, and have a different dynamic structure that expresses the characteristics of each character. The scenic design and the voice favor the character of Ze Pequeno, demonstrating his strength and showing his subjectivity, interfering by intonation, pause, loudness and speed of all other characters present in the scene. In Excerpt 3, divided into 3 parts, it was possible to observe that the movie language, interpretation and voice were modified in each of them. Conclusion: The assessment of the movie followed language differentiation in each one of the parts of the plot and, thus, the script, the moviemaking, songs, editing, interpretation and voice followed a specific style in each of them. The analysis led us to wondering that the speech and voice support provided to actors could go beyond the text, which would be triggered by similar experiences already lived by the actor, producing gestures and vocal manifestations resulting from these psychological or emotional experiences, and the technique employed would refine this previous and essential state of actors' work. The text (wording) would surface from other texts, formed by intentions, ideas, emotions and feelings, that is, text and voice would arise from the subtext.